(untitled) (MMIT Proceedings, 2025)
The purpose of this paper is to explore the concept of digital diplomacy and the role of the digital economy in promoting the development of small and medium-sized innovative enterprises in the Republic of Uzbekistan. Methodology. The research is based on a general scientific methodology with a systematic analysis of challenges. It draws on fundamental works of national and international scholars focusing on the digital economy, digital diplomacy, and innovation-driven business development in emerging economies, with a focus on Uzbekistan. Results. In Uzbekistan, the integration of digital diplomacy and the digital economy plays an important role in improving the ecosystem for small and medium-sized enterprises (SMEs). Through international cooperation and digital channels, Uzbekistan gains access to cutting-edge techniques, knowledge transfer, and global partnerships that foster innovation and entrepreneurship. However, progress continues to be hampered by a number of barriers, including weak digital systems, limited digital readiness among entrepreneurs, and inadequate connectivity to global digital nets. Despite these challenges, digital diplomacy serves as a strategic item to position Uzbekistan on the global step as a modern, innovation-oriented economy. It strengthens Uzbekistan’s potential to attract foreign investment, form international technique alliances, and enhance the global competitiveness of local SMEs. Practical implications. The findings of this study can be applied by small and medium-sized innovative enterprises in Uzbekistan, as well as by government agencies and international diplomatic missions engaged in economic cooperation and digital development initiatives. Conclusion. Digital diplomacy, in conjunction with the digital economy, exerts a profound influence on the development of small and medium-sized innovative enterprises in Uzbekistan. State policy focused on advancing digital diplomacy and fostering digital transformation is essential for reinforcing the country’s strategic position both in the domestic market and the global economy. Strengthening the country’s strategic position in both the domestic market and the glob al economy.